Evaluation of bridge-scour research : abutment and contraction scour processes and prediction - Sturm, Terry W. (NCHRP web document, 2011)
This report reviews the present state of knowledge regarding bridge-abutment scour and the veracity of the leading methods currently used for estimating design scour depth.